Parallel processing applied to the design of concrete encased grounding electrodes - Murta Vale, María Helena (2001)
This work presents the authors investigation regarding the application of parallel processing to the design of grounding systems, comprising concrete encased electrodes. The natural parallelism of the involved tasks and the large time-consuming characteristic of sequential processing for this kind of application justify the use of high performance computation. This design problem presents two main approaches for parallelism exploring. This work shows the advantages of parallel processing for generation of a geometric coefficient matrix, which describes the basic relations among currents and potentials at the grounding system. The grounding model has been developed at Federal University of Minas Gerais and, for implementing the parallel algorithm version, a computational tool (CPAR), which was developed in Polytechnic School of São Paulo University, was employed.